2016
DOI: 10.1016/j.agwat.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Modern viticulture in southern Europe: Vulnerabilities and strategies for adaptation to water scarcity

Abstract: b s t r a c tWater is now considered the most important but vulnerable resource in the Mediterranean region. Nevertheless, irrigation expanded fast in the region (e.g. South Portugal and Spain) to mitigate environmental stress and to guarantee stable grape yield and quality. Sustainable wine production depends on sustainable water use in the wine's supply chain, from the vine to the bottle. Better understanding of grapevine stress physiology (e.g. water relations, temperature regulation, water use efficiency),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 165 publications
(240 reference statements)
1
125
0
Order By: Relevance
“…In semi-arid areas exposed to water scarcity, re-using wastewater is an attractive practice to promote water and cost savings. However, water quality, mainly in regards of a too high salt concentration, inducing salt stress, can have detrimental effects on overall vineyard performance (Costa et al, 2016;Laurenson et al, 2012), more specifically on vine transpiration (Pereira et al, 2015) and can negatively affect yield and berry composition and consequently final wine quality (Miras-Avalos and Intrigliolo, 2017). Using moderately saline water for deficit irrigation, Degaris et al (2016) reported an effect on ion partitioning (Cl -, Na + , and K + ) in grapevines berries.…”
Section: Towards a Site-specific Deficit Irrigation Strategy?mentioning
confidence: 99%
“…In semi-arid areas exposed to water scarcity, re-using wastewater is an attractive practice to promote water and cost savings. However, water quality, mainly in regards of a too high salt concentration, inducing salt stress, can have detrimental effects on overall vineyard performance (Costa et al, 2016;Laurenson et al, 2012), more specifically on vine transpiration (Pereira et al, 2015) and can negatively affect yield and berry composition and consequently final wine quality (Miras-Avalos and Intrigliolo, 2017). Using moderately saline water for deficit irrigation, Degaris et al (2016) reported an effect on ion partitioning (Cl -, Na + , and K + ) in grapevines berries.…”
Section: Towards a Site-specific Deficit Irrigation Strategy?mentioning
confidence: 99%
“…In viticulture, the knowledge of the right soil water deficit to be applied to the vineyard is a key factor to obtain high quality wines (Costa et al 2016). Although the role of soil properties and management in wine production is acknowledged as determinant of terroir expression (van Leeuwen et al 2004), the soil component is generally perceived as secondary to climate and canopy management, and its influence on root water uptake is scarcely documented in the viticultural literature.…”
Section: General Overviewmentioning
confidence: 99%
“…Water stress in vineyards is a common phenomenon that occurs in the Western Cape of South Africa during the summer [1]. Water stress promotes stomatal closure [2], which inhibits photosynthesis and transpiration, leading to an increase in vine leaf temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%